2011
DOI: 10.2337/dc11-0103
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency Is Associated With Retinopathy in Children and Adolescents With Type 1 Diabetes

Abstract: OBJECTIVETo examine the hypothesis that vitamin D deficiency (VDD) is associated with an increased prevalence of microvascular complications in young people with type 1 diabetes.RESEARCH DESIGN AND METHODSIn a cross-sectional study of 517 patients, 25-hydroxyvitamin D was measured. Retinopathy was assessed by 7-field stereoscopic retinal photography, peripheral neuropathy by thermal and vibration threshold testing, and microalbuminuria by albumin excretion rate or albumin-to-creatinine ratio.RESULTSRetinopathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 13 publications
4
79
1
4
Order By: Relevance
“…In the National Health and Nutrition Examination Survey, for example, the diagnosis of peripheral neuropathy is based on self-reported symptoms of neuropathy, such as pain, tingling, numbness, or loss of feeling in hands or feet (19). In contrast, Kaur et al (20) reported a higher prevalence of vitamin D deficiency in patients with diabetic retinopathy but found no association between vitamin D deficiency and neuropathy or nephropathy.…”
Section: Discussionmentioning
confidence: 89%
“…In the National Health and Nutrition Examination Survey, for example, the diagnosis of peripheral neuropathy is based on self-reported symptoms of neuropathy, such as pain, tingling, numbness, or loss of feeling in hands or feet (19). In contrast, Kaur et al (20) reported a higher prevalence of vitamin D deficiency in patients with diabetic retinopathy but found no association between vitamin D deficiency and neuropathy or nephropathy.…”
Section: Discussionmentioning
confidence: 89%
“…1 Its deficiency has been associated with cancer, infection, asthma, dermopathies, 2 insulin resistance, diabetes and related microvascular complications 3 and retinopathy. 4 The effect in diabetes has been attributed to vitamin D action in promotion of the intestinal absorption of calcium and the secretion of insulin. 5 Vitamin D deficiency has even been postulated to be the factor underlying the health disparities often shown between African Americans and White Americans through the effect on paracrine and autocrine mechanisms that affect health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them [255][256][257][258][259][260][261][262][263][264][265], including the larger ones, but not all [258,264], found associations between low vitamin D levels and the presence and severity of diabetic retinopathy. In a cross-sectional study of the Children's Hospital at Westmead type 1 diabetes cohort, vitamin D levels were inversely associated with the presence diabetic retinopathy, which was assessed based on vascular lesions [261]. However, vitamin D levels were not associated with earlier biomarkers of retinal vascular geometry [266].…”
Section: Nutrition-related Biomarkersmentioning
confidence: 99%